90.3k views
4 votes
Find the first three output values of the fractal-generating function f(z)=z^2-3+2i

User Ed Webb
by
6.2k points

1 Answer

5 votes
Presumably, you would start with a given initial value which can generally be chosen to be
z_0=x+iy. Then you would find
z_3=f(z_2)=f(f(z_1))=f(f(f(z_0))). Symbolically, this expression will become quite cumbersome after just the first iteration.

So let's say
z_0=1. Then we have


z_1=f(1)=(1)^2-3+2i

z_1=-2+2i


z_2=f(-2+2i)=(-2+2i)^2-3+2i

z_2=-3-6i


z_3=f(-3-6i)=(-3-6i)^2-3+2i

z_3=-30+38i
User Nanno Langstraat
by
6.1k points